Hannah Kilham and Gender Issues: The Place of Females in the Liber-ated African Villages of Sierra Leone - Zizer, V. (Department for the Study of Religions, University of Ghana, 2018)
This paper examines how Kilham and her educational approach for Africans contributed to redefine the place of females in the Christianisation process of Liberated Africans in Sierra Le-one. The paper investigates some of the Colonial Government poli-cies for Liberated Africans in 19th century Sierra Leone to see how they served to define the place of females in the Liberated African villages. Various groups and individuals offered different forms of intervention to mitigate their challenges. Hannah Kilham, a 19th century English Quaker, was one such person who was committed to the cause of the Liberated Africans in Sierra Leone. She, like other agents, believed that education played a major role to introduce Christianity to Africans and to promote acceptable commerce among them. Unlike them, she maintained that for education to be meaningful to Africans, it must be offered through the medium of their own languages. Kilham’s approach contributed to the work of other agencies and directed them to the significance of focusing on girls’ education
Journal Article
Keywords: Friend; Inward light; Liberated; Native; Indigenous; Quaker; Kilhamite